Media Pembelajaran Video Tutorial Interaktif Berbasis Adobe Flash Pada Mata Kuliah Pemrograman Dasar - Irawan, Usman; Wirasasmita, Rasyid Hardi (Universitas Hamzanwadi, 2019)
feasible to be applied as learning media for C ++ Basic Programming,and knowing the feasibility of interactive video tutorial learning media to be applied as basic programming learning media for the University Hamzanwadi Program Study Education Informatics. This research is a research and development. The development model used is the ADDIE development model. The type of data used is quantitative and data collection techniques using a questionnaire. The data analysis technique in this research is quantitative descriptive. The results showed that the results of interactive tutorial video learning media products stated that it was appropriate to be used according to material experts with a percentage of 85% while according to media experts it was declared very feasible with a percentage of 89% and the results of user responses were stated to be Very High with a percentage of 83%. Thus the interactive video tutorial learning media is very feasible to be used as a learning media.